Review Volume, Consumer Ratings, and Rental Price in the Sharing Economy: The Case of Airbnb Jakarta - Christian Haposan Pangaribuan; Jalu Kawiworo (Ekonomi dan Bisnis, 2019)
Online reviews are emerging as a powerful source of information influencing consumers’ pre-purchase evaluation. This phenomenon has emphasized the need for a further comprehension of the impact of online reviews on consumer attitudes and behaviors, particularly in the sharing economy platforms. This study aims to examine the relationship of attributes in Airbnb listings towards online reviews and measure the effect of online reviews towards rental price. To examine the hypothesis and drawing conclusion, a web-crawling code was developed to collect data related with the characteristics of Airbnb’s listings, the attributes of the hosts, and the reputation of the listings. The model was tested by using a dataset of 413 Airbnb listings within Jakarta area over a period of Airbnb`s launch in January 2012 until May 2018. The data collected from the survey was processed and analyzed through multiple linear regression model, t-test, and f-test. The results of this study indicate that an online review is not a significant aspect in determining rental price of an accommodation. Furthermore, the findings highlight the importance of a “superhost” badge to influence review volume, while membership duration represents the key reason that affects both review volume and consumer ratings.